Clinical profile and outcome of children with Neuroblastoma: A single center retrospective study from North India - Zaibaish Khan; Nishant Verma (Pediatric Hematology Oncology Journal, 2025)
Background: With advances in pediatric oncology care, the outcome of children with neuroblastoma has improved. However, in low and middle-income countries (LMICs), the survival rate remains low. This study was conducted because of the paucity of data regarding the clinico-epidemiological profile and outcome of children with neuroblastoma in India. Methods: Children (<13 y) with neuroblastoma treated at our centre between 2016 and 2022 were retrospectively analyzed. Results: Over the 7-year study period, 53 children with neuroblastoma were treated at our centre. The age ranged from 1 month to 13 years (male: female ratio: 2.3:1). Adrenal was the most common primary site (58%). The majority of children had stage 4 disease (58.5%). The projected 2-year overall survival is 30%, whereas the event-free survival is 24.5%. Conclusions: Children with neuroblastoma in our setting presented late with advanced disease. Even with a multidisciplinary approach, the survival rate for patients with advanced disease were still poor.